Women’s Political Participation - Team of Researchers with a Woman Politician in Ibadan - Ademola-Adeoye, Feyisayo (Locating the Albatross in Women's Political Participation in Sub-Saharan Africa, 2021)
Video on plot study recorded in Ibadan, Oyo State
Keywords: Women; Sub-Saharan Africa; Political rights; Political participation; Structural Barriers; Political Barriers; Politics